骨皮质切开加速正畸牙齿移动对牙根吸收的影响 (Beijing Da Xue Xue Bao Yi Xue Ban, 2021)
In recent years, developing new methods to accelerate orthodontic tooth movement (OTM) has attracted extensive attention in the field of orthodontic clinical and scientific research. It reduces orthodontic treatment time and risks. Over the past, various approaches have been done to accelerate orthodontic tooth movement. Several forms of corticotomy techniques have been effective in inducing rapid tooth movement. These techniques activate regional acceleratory phenomenon and create a favorable microenvironment for accelerating tooth movement. Root resorption is one of most common side effects of orthodontic treatment. It affects the long-term viability and health of teeth. However, the effect of corticotomy techniques accelerating orthodontic tooth movement on root resorption still remains unclear. Accelerating tooth movement may have two-side effects on root resorption. Through shortening the treatment period and removing the hyalinized tissues, the acceleration of orthodontic tooth movement could reduce root resorption. The increase of root resorption might be due to the local inflammation and function of cementoclasts/odontoclasts. In this paper, we reviewed the effects of different corticotomy techniques accelerating orthodontic tooth movement on root resorption. Corticotomy techniques deal with mucoperio-steal flaps and bone tissues differently and develop towards minimally invasive. Previous studies on root resorption use two-dimensional images, including apical films and panoramic tomography, to evaluate the degree of root resorption. In recent years, researches measure the volume of root resorption accurately using cone-beam computed tomography (CBCT) and micro-CT. Most studies suggest that the root resorption during acceleration of orthodontic tooth movement through corticotomy techniques is not statistically different from that of traditional orthodontic treatment. Some studies using micro-CT have shown that the root resorption in the groups of corticotomy techniques increases compared with the control group without surgery. Because of the short duration of these studies, the clinical significance is controversial on the overall impact of corticotomy techniques on orthodontic treatment. Accelerating orthodontic tooth movement is still at its emerging phase and need further research in the form of clinical trials to illustrate the effect of corticotomy techniques accelerating orthodontic tooth movement on root resorption.